EUPHEMISMS OR LINGUISTIC DIPLOMACY (ON THE EXAMPLE OF UKRAINIAN AND GERMAN LANGUAGES) - Tkachivska, M. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article provides an overview of researches on euphemisms in modern Ukrainian and foreign linguistics. It studies classifications of euphemisms, names ways and techniques of translation of euphemisms from Ukrainian into German, provides examples, taken from works of modern writers. A euphemism is a kind of linguistic diplomacy, a tactful veiling or softening of something said which is pretty understandable for both the speaker and the listener. It is a so-called mask that provides a possibility to avoid unwanted taboos; it is a specific choice of words used in order to elevate the speaker’s utterances. A euphemism is a word or a word combination, which serves a purpose of an indirect nomination, it is a result of association with a certain object or phenomenon, and it shows a real culture level of a person. Euphemisms existence is caused mainly by fear and superstitions, which are connected with religious beliefs, prejudice etc. They are an important part of a verbal art and they are used in both oral and written texts. Euphemisms deal with spheres of politics, science, culture, education, and healthcare as well as with different aspects of human life. Ukrainian literature uses euphemisms concerning different spheres of a person’s life: his physical and spiritual state, mental abilities, and fear of death, diseases, social insecurity, family and personal relationships. Semantic subgroups of modern Ukrainian literature include political euphemisms, social status euphemisms, euphemisms dealing with family relations, education, intelligence level, euphemisms dealing with intimate sphere, as well as the ones connected with diseases, loss of life, criminal euphemisms etc. Translation of euphemistic phraseological units can be performed through the following main methods: 1) a euphemistic phraseological unit → a euphemistic phraseological unit, 2) a euphemistic phraseological unit → a neutral word, 3) a neutral word → a euphemistic phraseological unit.